2016
DOI: 10.1136/thoraxjnl-2016-208657
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms in people living with HIV and the effect of antiretroviral therapy: a systematic review and meta-analysis

Abstract: BackgroundAntiretroviral therapy (ART) has significantly altered the pattern of acute and chronic HIV-related disease. However, it is not clear what this means in terms of respiratory symptoms. We sought to investigate the association between HIV status and respiratory symptoms and how these have changed with the availability of ART.MethodsWe searched Cochrane, Medline and Embase databases for studies published between 1946 and August 2015 comparing the prevalence of respiratory symptoms in populations with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…As a result, AIDS-related morbidity and mortality have decreased markedly; however, aging with HIV has brought other challenges [ 1 ]. For instance, PLWH are more likely to develop chronic obstructive pulmonary disease (COPD) [ 2 ] and are also more likely to suffer from severe respiratory symptom burdens even after adjustment for smoking habits [ 3 ]. Although the pathogenesis of accelerated COPD in PLWH is poorly understood, the unique risk for pulmonary infections in this setting suggests that shifts in the lung microbiome might account for this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, AIDS-related morbidity and mortality have decreased markedly; however, aging with HIV has brought other challenges [ 1 ]. For instance, PLWH are more likely to develop chronic obstructive pulmonary disease (COPD) [ 2 ] and are also more likely to suffer from severe respiratory symptom burdens even after adjustment for smoking habits [ 3 ]. Although the pathogenesis of accelerated COPD in PLWH is poorly understood, the unique risk for pulmonary infections in this setting suggests that shifts in the lung microbiome might account for this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…This review reported that the best performing rule was the presence of any one of: current cough (any duration), fever, night sweats or weight loss with sensitivity of 78.9% (95% CI 58.3% to 90.9%) and specificity of 49.6% (95% CI 29.2% to 70.1%) . Another systematic literature review highlighted the importance of respiratory symptoms among HIV‐positive individuals , with a pooled odds ratio for the prevalence of cough of 3.05 (95% CI 2.24 to 4.16) among HIV‐positive compared to HIV‐negative individuals . HIV‐positive people remain at higher risk of respiratory symptoms even when started on ART, and are at increased risk of chronic lung disease from a variety of causes .…”
Section: Discussionmentioning
confidence: 99%
“…HIV‐positive people remain at higher risk of respiratory symptoms even when started on ART, and are at increased risk of chronic lung disease from a variety of causes . Ideally, advice on smoking cessation and links to specialist services providing diagnosis and management of infectious and non‐infectious causes of lung disease should be included as part of routine HIV care, along with regular screening for TB .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from London of 197 HIV positive and 93 HIV negative participants specifically evaluated the prevalence of respiratory symptoms with the St George's Respiratory Questionnaire (SGRQ) and Medical Research Council (MRC) dyspnoea scale. It found a greater frequency of respiratory symptoms in PLWH, with a median SGRQ of 12 (IQR 6-25) vs 6 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) in controls, p<0.001. (4) As the minimum clinically important difference between groups is usually regarded as four, (5) this suggests that the PLWH had more reported symptoms.…”
Section: Respiratory Symptoms and Hivmentioning
confidence: 94%